Habit persistence in effective tax rates - Harris, Mark; Feeny, S. (ROUTLEDGE TAYLOR & FRANCIS LTD, 2003)
This paper uses administrative data from the Australian Tax Office (ATO) to model the effective tax rates (ETRs) of large Australian corporates. The extent to which there is any habit persistence in ETRs is also examined. The results suggest that unobserved entity heterogeneity is important in explaining ETRs. In terms of observed heterogeneity, entity size, level of leverage, capital intensity, foreign income and R and D, are important explanators of ETRs. There is also evidence of a significant amount of habit persistence, implying that ETRs converge monotonically towards the statutory rate of corporation tax.